The ABC funding for the formation of the sale price in a laboratory of environmental analysis - Souza, Renan Rozeng de (2019)
The general objective is to present the results of a case study that analyzed the use of ABC costing for the formation of sale price in the provision of services of a laboratory of physical chemical analysis for environmental studies. To do so, a descriptive research was carried out with a qualitative approach, through a case study, participatory and documentary research based on income statements, inventories of fixed assets and studies of the demands and technical hours of the services rendered. The results showed that: a) the services rendered in this laboratory presented indirect costs in the ratio of 86% of total resources; b) the most representative resources refer to the labor force, which corresponded to 85% of total expenditures; c) the activity that presented the highest costs was to plan the samplings; and d) the service that has the highest cost is the PTS (Total Suspended Particle) Monitoring. The laboratory sales prices related to the services of Matrix 1 analyzes of atmospheric emissions in ducts and chimneys, are higher than those calculated based on the ABC cost, except for the analysis service for the determination of CO (Carbon Monoxide). The sales prices practiced for the services of Matrix 2 air quality monitoring at ground level, except for the noise evaluation, were below the values suggested in the study. It is concluded that this laboratory has its highest costs related to labor and that the ABC costing method is an adequate tool for the recognition of costs in this segment and contributes to the establishment of the sale price.